2014
DOI: 10.1088/0268-1242/30/1/015017
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching properties of manganese oxide nanoparticles with hexagonal shape

Abstract: Uniformly sized hexagonal shaped manganese oxide (MnO) nanoparticles were chemically synthesized. The bipolar resistive switching characteristics were investigated in the Ti/MnO/Pt structure. The nanoparticles were assembled as close-packed monolayer with a thickness of 30 nm by dip-coating and annealing procedures. The bipolar resistive switching behaviors in Ti/MnO/Pt device could be caused by the formation and rupture of conductive filaments in the nanoparticles. The temperature dependence of resistance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, poor electron conductivity limits its application into supercapacitors due to the low specific capacitance . As a typical semiconductor, manganese oxide has gained specific attention in electronic devices and supercapacitors thanks to its high bandgap, low cost, abundance, low toxicity, high theoretical capacitance (1370 F g −1 ), variable valence states, and stable chemical properties . As a typical rare earth based‐perovskite, the electrochemical behaviors of LaMnO 3 have been widely investigated owing to its stable thermal and structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, poor electron conductivity limits its application into supercapacitors due to the low specific capacitance . As a typical semiconductor, manganese oxide has gained specific attention in electronic devices and supercapacitors thanks to its high bandgap, low cost, abundance, low toxicity, high theoretical capacitance (1370 F g −1 ), variable valence states, and stable chemical properties . As a typical rare earth based‐perovskite, the electrochemical behaviors of LaMnO 3 have been widely investigated owing to its stable thermal and structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale electrodeposition and electrodissolution are dependent on the microscale to nanoscale features of the materials involved, and characterizing the atomic-scale effects that influence filament kinetics in situ is challenging. For a single filament, the process of formation has been studied experimentally through imaging with transmission-electron microscopy (TEM) and scanning-electron microscopy (SEM), by contact methods such as atomic-force microscopy, , and through atomistic simulations. ,, Prior work has usually examined filament formation as a function of the switching voltage, based on a voltage ramp ,, or voltage pulses, , with the general result that filaments formed at different voltages/currents also form at different times. However, these studies have not addressed either the complete initial formation of filaments, which is typically substantially different than subsequent formations, due to an initialization process, or the kinetic behavior of many filaments in parallel.…”
mentioning
confidence: 99%
“…A common theme in exploring conductive filament formation in ReRAM devices is the addition of nanostructures or nanoparticles within the electrolyte as a means of modifying the electric field distribution within the electrolyte/insulating material . Prior experiments have utilized nanostructures either attached to, or formed from, an electrode ,, or made from either insulators or conductors . In a suitable geometry, nanostructures could conceivably increase junction density by forming multiple junctions with one set of electrodes, more effectively using the available volume without additional electronics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 bipolar resistive switching due to the formation and migration of oxygen ions and the transport property of the device was attributed to ohmic, space-charge-limited current, and Schottky mechanism. 21 Some other scholarly articles are also available on resistive switching behaviors of manganese oxide based materials, 22−25 whereas a study on manganese sulfide has rarely been reported. 7 In this work, carbon nitride supported nanoparticles of manganese sulfide (CNMS) have been employed as an active component to fabricate a metal−insulator−metal type of device that exhibits a bipolar resistive switching behavior.…”
Section: ■ Introductionmentioning
confidence: 99%